Studi Kasus Pengaruh Kualitas Pengelolaan Terhadap Kriteria Malcom Baldrige Dan Kinerja Organisasi Di Unit Enterprise Segmen Manufacturing Divisi Enterprise Service PT Telkom - , SYAIFUDIN, Prof.Dr. Djoko Santoso M.S.A ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Manufacturing Segment Enterprise Unit (UNES MFG), Enterprise Service Division, PT. Telekomunikasi Indonesia, tbk represents part of PT. Telkom managed Customer Manufacturing segment enterprise. UNES MFG has started to implement quality management based on Malcolm Baldrige Criteria Framework. Malcolm Baldrige Framework represents a framework commonly used for measuring organization or company quality based on 7 (seven) dimensions), namely : leadership, strategic planning, customer & market focus, measurement-analysis & knowledge management, workforce focus, process management and results. Therefore for covering whether any influence of organization management on performance improvement in Malcolm Baldrige criteria framework, it is necessary to conduct research at UNES MFG as research object. This type of research is case study with way of distributing questionnaire survey, statistic test on survey data for viewing the influence of both independent variables (organization performance and Malcolm Baldrige criteria) and one dependent variable (organization quality). The form of data examination is through validity and reliability test, while for viewing the influence is through linear regression test and independent variable correlations is through multiconlinearity test. SWOT analysis was conducted based on observation for giving current internal condition view and UNES MFG external situation. Research result shows all questions asked in survey of seven (7) Malcolm Baldrige criteria is valid and reliable. While statistic test shows that the influence of inter-variable population measure can be said significant. SWOT analysis shows that planning strategic and after sales service aspects is needed to be done improvement. The achievement of Malcolm Baldrige criteria scoring of UNES MFG in 2009 is 580.25 and placing Emerging Industry Leader level. Through this research, it is expected any benefit especially for UNES MFG, Service Enterprise Division, PT. Telkom, Tbk in improving organization management quality for increasing Malcolm Baldrie Criteria score and organization performance. It is expected that UNES MFG can use the existing strength and opportunigy as well as capable to minimize weakness and avoid the future threat.